The use of an application to record information on Dentistry patients from the perspective of dental surgeons - Regina Tavares, Aglae; Mónica Caetano, Anne; Monken de Assis, Sonia Francisca; Jansiski Motta, Lara (Revista Cubana de Información en Ciencias de la Salud, 2018)
Dental records are complex documents and not all dental surgeons have been careful to fill them correctly. On the other hand, a number of apps for professional support has been observed on the market aimed at healthcare. The purpose of this study was to show how dental surgeons have noticed the technology of mobile devices and how it would help in their work routine by analysing an application for recording patient information. This study was exploratory, qualitative, descriptive, and transversal, with data obtained through a semi-structured interview with open-ended questions applied to ten dental surgeons who have downloaded the App ‘OdontoExame’ as study population. The answers were analysed by the content analysis technique. The results showed that this technology could be useful in storing information. Besides, 90% of respondents stated that the application would help in clinical practices, while 10% considered such a technology still limited to this function.